2018
DOI: 10.1080/21663831.2018.1434248
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and properties of high-entropy alloy films and coatings: a review

Abstract: In the past 14 years, as a branch of high-entropy alloy (HEA) materials, HEA films and coatings have exhibited the attractive and unique properties, relative to the conventional film and coating materials. The recent research and development of HEA films and coatings are reviewed in this paper. At first, the basic concept of HEAs films and coatings are introduced. Then, their preparation technologies, microstructures and appealing properties are summarized. Moreover, the possible reasons and design criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 424 publications
(101 citation statements)
references
References 182 publications
(286 reference statements)
0
101
0
Order By: Relevance
“…The investigation results of the hardness of the coatings indicate that a significant increase in hardness is observed with nanoscale thickness of the layers, which is achieved with continuous rotation of the substrate. This can be attributed to the size effect [5]. In addition, an increase in the partial pressure of nitrogen during coating deposition also leads to an increase in the nitrogen content in the coatings and, as a consequence, to an increase in the hardness of the coatings [6].…”
Section: Resultsmentioning
confidence: 99%
“…The investigation results of the hardness of the coatings indicate that a significant increase in hardness is observed with nanoscale thickness of the layers, which is achieved with continuous rotation of the substrate. This can be attributed to the size effect [5]. In addition, an increase in the partial pressure of nitrogen during coating deposition also leads to an increase in the nitrogen content in the coatings and, as a consequence, to an increase in the hardness of the coatings [6].…”
Section: Resultsmentioning
confidence: 99%
“…Application of protective coatings may bring an increase of corrosion and chemical resistance [66,67], increase of working temperature of the products [68], improved wear resistance [69,70] and, thus, longer lifetime of the product. Very high interest nowadays is on multi-layered structures [71][72][73] and high entropy alloy (HEA) coatings [73,74].…”
Section: Protective Coatingsmentioning
confidence: 99%
“…HEAs are a high-entropy solid-solution phase alloy formed by five or more principal elements, each of which has an atomic concentration between 5-35 at.% (atomic percent). The HEAs are not inclined to form intermetallic compounds due to their high-entropy effect, which tend to stabilize the simple body-centered-cubic (BCC), face-centered-cubic (FCC), or hexagonal-close-packed (HCP) solid solution [7][8][9][10][11][12]. A large number of subsequent studies have shown that HEAs have many superior properties than conventional alloys, such as the high strength, great hardness, strong wear resistance, good fatigue resistance, high oxidation and corrosion resistance [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%